Psychometric evaluation and factor structure of the Persian coping strategies questionnaire in chronic low back pain patients - Sarvenaz Karimi-GhasemAbad; Behnam Akhbari; Mahyar Salavati; Saeed Talebian Moghaddam; Ahmad Saeedi; Mahsa Seydi; Mohammad Ali Shakoorianfard (Journal of Current Oncology and Medical Sciences)
Introduction: This study aimed to investigate the factor structure and psychometric properties of the Coping Strategies Questionnaire (CSQ) in Persian in people with non-specific chronic low back pain (NSCLBP).